MODERATING ROLE OF INTERNATIONALIZATION AND FIRM SIZE ON THE RELATIONSHIP BETWEEN INSTITUTIONAL OWNERSHIP AND EARNINGS QUALITY - Moonmuang, Kingkan; Dampitakse, Kusuma; Ngudgratoke , Sungworn (RMUTT Global Business and Economics Review, 2025)
This study examines the moderating effects of internationalization and firm size on the relationship between institutional ownership and earnings quality. The sample consisted of 326 firm-year observations from four industries listed on the Stock Exchange of Thailand (SET) during the period 2017–2019. The findings revealed that institutional ownership did not have a significant effect on earnings quality. However, internationalization positively moderated this relationship, while firm size did not exhibit such an effect. Further analysis indicated that institutional ownership was positively and significantly associated with earnings quality only in firms that operated internationally and were of medium to large size. These results point to the value of effective corporate governance mechanisms, particularly for firms expanding into international markets with institutional investors as shareholders. The study contributes to a more profound understanding of the conditional factors affecting earnings quality in emerging market contexts.